Peace by Neighborhood: Rukun Tetangga sebagai Asosiasi Persatuan Kejiranan dan Potensi Praktikalnya terhadap Hubungan Antar Etnik di Malaysia dan Indonesia - Khaidir, Afriva (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2006)
Ethnic relation, particularly between the Malay as indigenous people and the Chinese in some Southeast Asia countries, is one of the most important aspects in an effort to compose a nation. Focusing on discourse of the role of social organization in maintaining peace in society, a research has conducted in Alor Setar, Malaysia and Padang, Indonesia, two cities with different colonial administration in the past, British and Dutch. A qualitative-quantitative research was conducted to explore the potencies of the neighborhood association in creating peace through ethnic relations between Malay and Chinese. The scheme facilitates contacts and engages people of community by various activities. Those performances in core activities have been evaluated positively by the citizens. Nevertheless, some social aspects became problematic in connecting the people through civic engagement of the ethnic groups. The management of the Rukun Tetangga in the two countries is also different. However, as a neighborhood association, Rukun Tetangga has eminent role in maintaining supportive social relationship between ethnic groups in a community. Kata Kunci: Rukun Tetangga, Hubungan antar Etnik, Perpaduan, Konflik, Kejiranan